Delay of insulin initiation in patients with type 2 diabetes mellitus inadequately controlled with oral hypoglycemic agents (analysis of patient‐ and physician‐related factors): A prospective observational DIPP‐FACTOR study in Korea. Issue 3 (30th March 2017) - Kim, Sin Gon; Kim, Nam Hoon; Ku, Bon Jeong; Shon, Ho Sang; Kim, Doo Man; Park, Tae Sun; Kim, Yong‐Seong; Kim, In Joo; Choi, Dong Seop
Abstract : In real clinical practice, insulin initiation is delayed in majority of patients with type 2 diabetes who were uncontrolled on two or more oral hypoglycemic agents. Patient‐related factors for delay in insulin initiation were older age, shorter duration of diabetes, and lower HbA1c. Physician‐related factors were age (˜50 to <60 years), female sex, and smaller number (<1000) of patients consulted per month. Abstract: Aims/Introduction: To assess the time to initiation of insulin therapy, and concurrently investigate both patient‐ and physician‐related factors associated with delaying insulin therapy in Korean patients with type 2 diabetes uncontrolled by oral hypoglycemic agents (OHAs). Materials and Methods: This prospective, observational disease registry study was carried out across 69 centers in Korea. Type 2 diabetes patients who had received two or more OHAs within the past 5 years, had a glycated hemoglobin ≥8% in the past 6 months and had not received insulin were included. Data recorded on data collection forms during a 12‐month period were analyzed. Results: Of 2168 patients enrolled, 1959 were evaluated and classified as the insulin‐initiated or insulin‐delayed group. Insulin was prescribed for just 20% of the patients during a 1‐year follow‐up period, and less than half (44.5%) of the patients who were taking two OHAs started insulin after 6 years. Patient‐related factors for delay in insulin initiation included older age, shorter duration of diabetes and lower glycated hemoglobin. Physician‐related factors included age (~50 to <60 years), sex (women) and number (<1000) of patients consulted per month. Patient refusal (33.6%) and physicians' concerns of patient non‐compliance (26.5%) were the major physician‐reported reasons for delaying insulin therapy. Inconvenience of insulin therapy (51.6%) and fear of injection (48.2%) were the major reasons for patient refusal. Conclusions: Insulin initiation is delayed in patients with type 2 diabetes uncontrolled by two or more OHAs in Korea. Patient‐ and physician‐related factors associated with this delay need to be addressed for better diabetes management.